THE IMPACT OF MONEY SUPPLY AND THE INFLATION RATE ON INDONESIA COMPOSITE INDEX: CASE STUDY IN INDONESIA STOCK EXCHANGE 2008-2017 - Sumaryoto Sumaryoto; Anna Nurfarkhana; Tri Anita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research is a descriptive and explanative research on the impact of money supply and the inflation rate on Indonesia Composite Index or IHSG. This research tries to understand the factors affecting the composite stock price index of IHSG by studying Indonesia stock exchange in the period of 2008-2017. The result of this study shows that: 1) The Amount of Money supply has a significant effect on the IHSG. This is evidenced by sig 0.00 < 0.05 and Fcount of 35.467 with the determinant coefficient (R2) of 0.947. This means that 94.7% of the impact is determined to be the contribution of the independent variable (Amount of Money supply and Inflation Rate) together on the dependent variable (IHSG). While the rest (5.3%) is the influence of outside variables not examined in this research. 2) The Amount of Money supply has a significant effect on the IHSG, in accordance with the hypothesis. This is evidenced by sig 0.00 < 0.05 and tcount of 9.213 for the regression coefficient of 0.131 with a significance level of 5% and a significance value of 0.00 (smaller than the significance level of 0.05). 3) The inflation rate has no significant effect on the IHSG. This is evidenced by sig 0.277 > 0.05 and tcount of 1.195 for the regression coefficient of 0.336 with a significance level of 5% and a significance value of 0.227 (greater than the significance level of 0.05).